The outdoor art room. Autumn - Storey Rita (London; Franklin Watts, 2018)
"Get outdoors and unlock your creative side with these fantastic art projects for autumn. Follow the step-by-step photographs to make a bug hotel, water colour leaves, a seed picture and lots more. Plus, find out all about autumn with the seasonal fact panels. The Outdoor Art Room is designed to get children out into the fresh air and interacting with nature. A range of simple arts and crafts projects as well as fun activities help them discover new things about their environment and the seasons at the same time as being active and having fun. Care is taken to ensure that these projects do not create any adverse environmental impact."
Keywords: Juvenile works